Transmisi Pemaknaan Al-Qur’an Dalam Sekar Sari Kidung Rahayu Karya Eyang Achmad Djuwahir Anomwidjaja - avip nurdarmawan; Muhammad Irfan Riyadi (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo Indonesia, 2024)
This research aims to describe Sekar Sari Kidung Rahayu and determine the transmission of science that occurs in this work. In this research the author used a qualitative descriptive research method. The results of this research are first, Sekar Sari Kidung Rahayu by Eyang Achmad Djuwahir Anomwidjaja is a tembang macapat which was composed as a form of response, appreciation and reception for the presence of the Qur'an in his cultural group. This work contains the meaning of the Qur’an , invitations and advice in studying the Qur’an . The completed work consists of Surah Al-Fatihah, An-Naba' – An-Nas (Juz 'Amma), Yasiin, Al-Baqarah, Ali-Imron and pieces of verses from the Qur’an . Second, the transmission of science that occurs consists of three stages: 1) Eyang's awareness of his cultural group which perpetuates the macapat tradition alongside the existence of pesantren as centers of Islamic religious education. 2) Interest in the form of Eyang's idea to compose tembang macapat containing meaning from the Qur’an . 3) Adoption takes the form of Eyang's actions as a transmitter in implementing ideas in his work. The meaning of the Qur'an by Eyang Achmad Djuwahir was then transmitted to the general public in the form of books, audio-visual documentation in digital media and through the Macapat community which studied Sekar Sari Kidung Rahayu. Keywords : tembang macapat, reception of the Qur’an, transmission of science.